American Guild of Variety Artists.: hearings before the United States Senate Committee on Government Operations, Permanent Subcommittee on Investigations, Eighty-Seventh Congress, second session. - United States. (U.S. G.P.O., 1962)
Investigates American Guild of Variety Artists administration and its union contracts with nightclubs.
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VII
Investigates American Guild of Variety Artists administration and its union contracts with nightclubs.
Keywords: Governmental investigations / United States.